Temperature and pressure effect on the anisotropy of dielectric permeability in KDP and DKDP crystals - Kedyulich, V.M.; Slivka, A.G.; Gerzanich, E.I.; Guivan, A.M.; Lukach, P.M. (Condensed Matter Physics, 2003)
Temperature dependences of longitudinal and transverse dielectric permeability of KDP and DKDP crystals are studied at different values of hydrostatic pressure in order to determine the pressure behaviour of the isotropic point for these crystals. The isotropic point temperature in KDP crystals at atmospheric pressure is Ti = 186 K at the measuring field frequency 1 kHz and Ti = 176 K at the frequency of 1 MHz. In DKDP crystals the isotropic point is achieved at the temperature Ti = 300 K ( 1 kHz) and Ti = 253 K ( 1 MHz). The hydrostatic pressure increase results in the reduction of the isotropic point temperature with the pressure coefficients ∂Ti/∂p = −4.3 K/kbar for KDP and ∂Ti/∂p = −2.9 K/kbar for DKDP. The analysis of the experimental results in the framework of the Blinc-Zeks pseudospin formalism has shown a good agreement between the calculated and the experimentally obtained temperature of the isotropic point for KDP crystals.